A Phenomenological Study of Teachers' First-Year Experiences of Curriculum Development in Christian International Schools. (August 2022) - Pedigo, Rachel Morgan; Smith, Samuel
The purpose of this phenomenological study was to explore the experiences of eight American teachers in Christian international schools during the process of developing curriculum during their first year of teaching. In light of the purpose of the study, the following research questions framed this investigation: How do teachers describe their experiences of developing curriculum during their first year of teaching at an international Christian school? What challenges do first-year teachers encounter when beginning to develop curriculum for their classes? What are first-year teachers' expectations of support during curriculum development? How do teachers describe their first-year experiences of adjusting to a new culture while at the same time working to develop curriculum? Participants for this study were purposefully selected classroom teachers who had been teaching at an Association of Christian Schools International (ACSI) international school for at least one year, but no more than three years. The theories guiding the study were experiential learning theory and the theory of cultural intelligence. Data collection methods included analysis of school documents, a photo narrative, and interviews. Data analysis procedures followed a heuristic research approach. The following themes emerged as a result of analyzing teacher interviews, photo narratives, and curriculum documents: (a) decision to teach internationally, (b) first year challenges teaching overseas, (c) effects of living cross-culturally, (d) developing curriculum at an international school, and (e) challenges to developing curriculum in an international school.